The Effect of Low-Intensity Hairmyres Exercises on Six-Minute Walk Distance in Patients with Chronic Obstructive Pulmonary Disease: A Preliminary Study - Nury Nusdwinuringtyas; Johan Talesu; Anita Ratnawati; Sabarinah B. Prasetyo (Indonesian Journal of Physical Medicine & Rehabilitation, 2020)
ABSTRACTIntroduction: Therapeutic exercise is the main rehabilitation program in patients with ChronicObstructive Pulmonary Disease (COPD). Shortness of breath due to persistent obstruction causesdisability in the form of decreased functional capacity. Hairmyers is an isolated group of exercise torecondition the limb muscles without weights. The purpose of this study was to assess the efficacy oflow-intensity Hairmyres exercise in improving Six-Minute Walk Distance (6MWD).Methods: This is a pre-post interventional study held from January to April 2005. Hairmyres exerciseswere given to the patients (n=14) with moderate and severe COPD for eight weeks, five times a weekwith two exercises performed in front of the researcher. Six-Minute Walk Distance was measured before,at the end of the 4 th week, and after the exercise program.Results: Compared to the beginning, the 6MWD increased by 27 meters at the end of the 4th week and62.29 meters at the end of the program in moderate COPD patients, while the increase in severe COPDpatients were 39.71 and 76 meters, respectively. There was a significant difference (p <0.05) betweenthe first and the last measurement in both groups. This difference also surpassed the minimal clinicallyimportant difference (MCID) of 6MWD.Keywords: COPD, Hairmyers, Low-Intensity Exercise, 6MWD